Cross‐linking enhanced room‐temperature phosphorescence of carbon dots. Issue 2 (2nd June 2022) - Wang, Boyang; Sun, Zhen; Yu, Jingkun; Waterhouse, Geoffrey I. N.; Lu, Siyu; Yang, Bai
Abstract: Currently, there is a strong drive to discover alternative materials that exhibit room‐temperature phosphorescence (RTP) for displays, bioimaging, and data security. Ideally, these materials should be nontoxic, cheap, and possess controllable photoluminescent properties. Carbon dots (CDs) possess each of these characteristics, but to date, less attention has been paid to their RTP mechanism. Herein, we synthesized a series of CDs by self‐crosslinking and carbonization of precursor. The resultant CDs were luminescent and exhibited a bright, micro‐second afterglow lifetime. To increase the RTP, a second microwave processing step was used to coat the CDs with polyvinyl alcohol (PVA), polyacrylamide (PAM), or tetraethyl orthosilicate (TEOS), producing CDs@PVA, CDs@PAM, and CDs@TEOS composites. The core–shell structure acted to enhance crosslinking at the surface of the CDs to boost the RTP, creating abundant energy levels for intersystem crossover. In situ X‐ray photoelectron spectroscopy verified electron transfer during luminescence. Finally, we present a design rule that can be used to tune the quantum yields and RTP lifetime of CDs, based on the effective stabilization of triplet excited states through the extent and strength of cross‐linking. This simple strategy provides a flexible route for guiding the further development of CDs with tailored RTP properties for various applications. Abstract : We propose a method to enhance phosphorescence emission by crosslinking. By controlling the degree and strength of crosslinking, the phosphorescence emission of carbon dots (CDs) can be tunable, and the CDs with the highest degree of crosslinking achieve a quantum yield of 55.49 and a lifetime of 750 ms.